Influencia de los medios de comunicación y el riesgo de padecer trastornos de la conducta alimentaria en escolares mujeres en Lima, Perú - Lazo Montoya, Yessenia (2015)
Introduction. Eating disorders (EDs) are a public health problem, and their relationship to mass media is still controversial. Objective. To assess whether there is an association between models of body image shown in mass media and the risk of developing EDs among female adolescent students from Lima, Peru. Methodology. Cross-sectional study conducted in three schools located in the district of La Victoria, Lima, Peru. The risk of developing EDs was measured using the Eating Attitudes Test-26 (EAT-26), while mass media influence was measured using the Sociocultural Attitudes Towards Appearance Questionnaire-3 (SATAQ-3), which was categorized into tertiles both in the overall score and its subscales (information, pressure, general internalization, and athletic internalization). Adjusted prevalence ratios (aPR) for EDs were estimated. Results. Four hundred and eighty-three students were included, their median age was 14 ± 3 years old. A risk of developing an ED was observed in 13.9% of them. Students who are more influenced by mass media (upper tertile of the SATAQ-3) have a higher probability of having a risk of developingan ED (aPR: 4.24; 95% confidence interval [CI]: 2.10-8.56), as well as those who have a greater access to information (PR: 1.89; 95% CI: 1.09-3.25), suffer more pressure (PR: 4.97; 95% CI: 2.31-10.69), show a greater general internalization (PR: 5.00; 95% CI: 2.39-10.43), and show a greater level of athletic internalization (PR: 4.35; 95% CI: 2.19-8-66). Conclusion.The greater the influence of mass media, the greater the probability of having a risk of developing an ED among female students from Lima, Peru.